PENYELESAIAN SENGKETA PHK TANPA PERUNDINGAN BIPARTIT PADA PENGADILAN NEGERI KOTA SEMARANG (STUDI PUTUSAN NOMOR 56/PDT.SUS-PHI/2019/PN SMG): Settlement of Layoff Disputes Without Bipartite Negotiations at the Semarang City District Court (Study of Decision Number 56/Pdt.Sus-PHI/2019/PN Smg) - Adriani, Kania; Pamungkas, Yogo (AMICUS CURIAE, 2024)
Termination of employment is an event that is very feared for employees because it involves loss of livelihood. One of the disputes in industrial is the layoff dispute. In the settlement of layoff disputes, there are several stages carried out, including Bipartite, which stage cannot be missed by both parties, whis stage of industrial relations dispute settlement must be carried out. The problems in this study are how the process of resolving layoff disputes between Fauzizah and PT Hansae Ace Apparel and whether the process of resolving layoff disputes between Fauzizah and PT Hansae Ace Apparel is in accordance with Law Number 2 of 2004. To get the answers above, a type of research is used. Normative law based.